Pengembangan Koleksi Pustaka Dinas Perpustakaan dan Kearsipan Kabupaten Mojokerto - Ucik Fitrialutfiana; Imam Suyitno; Taufiq Kurniawan (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2023)
The library collections of the Mojokerto Regency Library and Archives Service consist of print and digital. The print collection consists of general collections, references, local culture and serial publications. Digital collections are e-books on the e-pusda application. The library collection development strategy of the Mojekerto Regency Library and Archives Service is divided into 5 stages, namely: user analysis, collection development policies, selection of library materials, procurement and weeding. User analysis based on the characteristics and information needs of users through forms distributed to users. The library does not yet have written technical guidelines for development of SOPs, POBs or technical guidelines and field instructions. The library selects the print collection and pays attention to the criteria in terms of content, title, year of publication and publisher. Libraries focus on two methods, namely purchases and grants. The criteria used in weeding and enumeration were only collections that were damaged and misplaced with a frequency of once a week. The feasibility of developing library collections is based on the SNP-district/city libraries contained in PERKAPERPUSNAS No. 08 of 2017 shows that four points in the national standard are not in accordance with what is happening in the field, namely the first, second, third, and fifth items in the field, while the fourth and fifth items are in accordance with what is happening in the field.